Protection of Landowners' Rights in the Implementation of Pipeline Access at the Fuel Terminal in Baubau City - Ania Sudin; Safrin Salam; Eko Satria (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the legal relationship between landowners and Fuel Terminal operators in Baubau City regarding pipeline access practices, and to formulate an ideal legal protection model for affected landowners. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, field observations, and documentation studies, subsequently analyzed using the Miles et al. interactive model. The findings reveal that community land use for pipeline routes occurs without authentic deeds, comprehensive written agreements, or continuous compensation mechanisms, thereby creating a condition of nuda proprietas alongside juridical defects that open broad civil liability exposure through unlawful acts and strict liability doctrine. This condition substantively constitutes indirect expropriation, contravening Article 28H paragraph (4) of the 1945 Constitution. The ideal legal protection model requires the formalization of comprehensive land access agreements and the strengthening of regionally-based regulations grounded in distributive justice. From an SDGs perspective, this legal uncertainty perpetuates structural poverty and governance deficits, running counter to Goals 1, 10, 11, and 16.